Inflammatory cytokines, vitamins C and E in children versus adolescences with atopic dermatitis - Kamel, Iman Husein; Sabry, Rania Nabil; Abdel Hamid, Enas Raafat; Aly, Hanan Farouk; Ahmed, Hanaa Hamdy (Journal of Pediatric Biochemistry, 2014)
Atopic dermatitis (AD), a chronic inflammatory skin disease with no cure, currently affects almost one-fifth of the population of industrialized nations. Treatment can be challenging for physicians and patients, making it even more difficult to find safe therapeutic options, especially in severe disease. Interest in diet and nutrition has increased during the last few years. Nutritional interventions are both intriguing and accessible for many patients. AD has two phases, acute and chronic. No therapeutic attempts has yet been tried to target these phases rather than treatment according to severity grade. Studies point to interleukin (IL)-18 as key player in the pathogenesis of AD and the switch between its two phases. T helper (Th) cytokines (IL-4, IL-10, IL-12, IL-18), interferon-γ (IFN-γ), tumor necrosis factor-α (TNF-α), immunoglobulin E (Ig E), and vitamins E and C in children and adolescents with acute and chronic AD. Sixty AD patients were classified into two groups; children (acute) and adolescents (chronic) AD, with thirty in each. In addition, two corresponding healthy normal control groups of thirty each were evaluated. Serum IL-4, IL-10, IL-12, IL-18, IFN-γ and serum IgE were estimated by ELISA. IL-12, IL-18 and IFN-γ levels were 2–C-4 folds higher in chronic AD as compared to normal controls. IL-18 and TNF-α levels were significantly higher in chronic than acute AD patients. Vitamins C and E, on the other hand, were significant decreased in chronic versus acute AD patients. Conclusion: ILs, IFN-γ, TNF-α and serum IgE may play a role in AD. In addition, measurement of IL-18 may be a valuable tool for assessment of age related disease severity. Also, vitamins C and E appear to be reduced in acute and chronic AD patients.
Keywords: Atopic dermatitis; interleukins; TNF-α; INF-γ; vitamins C and E